2016
DOI: 10.1007/s00216-016-9676-8
|View full text |Cite
|
Sign up to set email alerts
|

Single Particle ICP-MS: Advances toward routine analysis of nanomaterials

Abstract: From its early beginnings in characterizing aerosol particles to its recent applications for investigating natural waters and waste streams, single particle inductively coupled plasma-mass spectrometry (spICP-MS) has proven to be a powerful technique for the detection and characterization of aqueous dispersions of metal-containing nanomaterials. Combining the high-throughput of an ensemble technique with the specificity of a single particle counting technique and the elemental specificity of ICP-MS, spICP-MS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
214
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(232 citation statements)
references
References 136 publications
3
214
1
1
Order By: Relevance
“…Our prior research has shown that the ICP-MS response to Au + in the thiourea/mixed acid was within 5% of that in water, thus the use of thiourea-based diluent for Au + standards is an unlikely source of the observed differences between η n−F and η n−S [40]. Others have reported an increase in Au + sensitivity in the presence of HCl [27], which suggests that matrix-induced biases differ depending on the ICP-MS sample introduction system, i.e. the nebulizer and spray chamber combination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our prior research has shown that the ICP-MS response to Au + in the thiourea/mixed acid was within 5% of that in water, thus the use of thiourea-based diluent for Au + standards is an unlikely source of the observed differences between η n−F and η n−S [40]. Others have reported an increase in Au + sensitivity in the presence of HCl [27], which suggests that matrix-induced biases differ depending on the ICP-MS sample introduction system, i.e. the nebulizer and spray chamber combination.…”
Section: Resultsmentioning
confidence: 99%
“…However, substantial matrix effect on NPs can be problematic if NP suspensions for spICP-MS measurement are dispersed in biological or environmental media containing a high content of matrix (e.g., phosphate-buffered saline, sea water, etc. ), which may require sensitivity correction using isotopic dilution analysis [60] or matrix matched ionic standards [27]. For samples that need additional dilution in water or the proposed diluents from this study, the matrix effect on NPs is expected to be low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cell culture assays, it is, however, possible to determine the cell number per sample size and thus extrapolate the NP quantities per cell number. However, ICP-MS has been advanced as single particle ICP-MS, which enables the distinction between the dissolved and particulate form of NPs, yet is it has not been revealed to what extend the complex biological matrix affects the signal produced from an NP and hence influence the measurement; the technique requires further development [14]. Nevertheless, such an approach for quantification of mass using elemental analysis techniques is a reliable tool to assess the material mass within a defined sample volume.…”
Section: Np Quantification Techniques: Some Illustrative Examplesmentioning
confidence: 99%
“…It is often difficult using existing techniques to characterize the properties of ENMs within foods because food matrices have such complex compositions and structures, and complete characterization of ENMs in food matrices may require development of new methods (Bellmann et al , 2015; Szakal et al , 2014a). Other analytical tools that might be used to provide valuable information about nanoparticle characteristics in the complex milieu of the GIT include Surface-enhanced Raman spectroscopy (SERS) (Taylor et al , 2016), single particle inductively coupled plasma mass spectrometry (sp-ICP-MS) (Ma et al , 2016; Montano et al , 2016), Field flow fractionation (FFF) (Laborda et al , 2016; Zattoni et al , 2014), X-ray absorption near edge structure (XANES) (Grafe et al , 2014; Kuzmin and Chaboy, 2014) and scanning and transmission electron microscopy (SEM and TEM).…”
Section: Ienm Property Transformations: Impact Of Food Matrix Effectsmentioning
confidence: 99%